Relationship of Financial Development, Globalization and Gender Inequality in Emerging Islamic Countries - Suhel, Suhel; Hidayat, Ariodillah; Yulianita, Anna; Teguh, Muhammad (Ekonomika, 2025)
This study analyzes the influence of financial development and globalization on the gender inequality index in emerging Islamic countries. The sample of this study is Islamic countries with emerging market categories, including Malaysia, Indonesia, Türkiye, Saudi Arabia, Pakistan, Qatar, Egypt, Nigeria, and Iran. These countries are sampled in this study based on the magnitude of their GDP in the Islamic emerging countries group. The analysis technique in this study uses a panel data regression. The results show that financial institution access, depth, and efficiency, as well as the KOF globalization index are proven to be able to reduce the gender inequality index. Expansion of the network of financial institutions to remote areas is deemed to improve access for women, with special attention to women in emerging Islamic countries.